Automated car braking system using fuzzy logic controller - Mamat, Marhatinie (2007)
This paper deals with a Fuzzy Logic Controller (FLC) for an automated car braking system. The response of the system will be simulated by using Fuzzy Logic Toolbox in MATLAB and PID controller. The purpose of this controller is to brake a car when the car approaches for an obstacle at a specific range. For this, the Fuzzy Logic Controller is design using the Fuzzy Logic Toolbox in MATLAB. The system uses four rules and three membership function. The two parameters such as distance and speed will be observed for both controllers and the ability to attenuate disturbance will be simulated. Output of the controller will determine the force of the car brake. Base on the simulation, it can be concluded that the response of Fuzzy Logic Controller is better than PID. However, PID controller can be used to constitute a reference for the performance of the fuzzy logic controller.